Seniška pesmarica iz 1864 - Kozar-Mukič, Marija (Traditiones (Ljubljana), 1999)
In the period between the 17th and the 20th centuries about one hundred hymnal manuscripts originated in the areas of Prekmurje in Slovenia and Porabje on the Hungarian side of the border. 18 of the 76 songs in the Catholic hymnal manuscript from Martjanci. New year's carol "Naraudo Szeje Kráo Nebeszky" (Born Was the King of Heaven), which is the translation of the Hungarian carol from the 16th century, reveals old age and possibly also the origin of the Custom
Keywords: ethnology; etnologija; ljudsko slovstvo; oral literature; ljudske pesmi; Ethnopoetics